How to deal with maternal and perinatal anemia - Urquizo Aréstegui, Raúl (2019)
The World Health Organization notes that anemia affects 1 620 million people in the world (1), the most affected are school-age children and pregnant women. Our country is no stranger to this reality. Anemia remains a public health problem, especially in children under 3 years old and in women of childbearing age. According to ENDES 2018, the indicators of anemia in children under 36 months were 43.5% nationwide, and in cities like Puno it reached 66.7%, in Arequipa, Moquegua at 33.9% and in Lima at 35 ,5%; 21.1% of women of childbearing age have anemia (2).